2018
DOI: 10.1115/1.4040044
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Computational Analysis of Right Ventricular Mechanoenergetics

Abstract: Right ventricular (RV) failure, which occurs in the setting of pressure overload, is characterized by abnormalities in mechanical and energetic function. The effects of these cell- and tissue-level changes on organ-level RV function are unknown. The primary aim of this study was to investigate the effects of myofiber mechanics and mitochondrial energetics on organ-level RV function in the context of pressure overload using a multiscale model of the cardiovascular system. The model integrates the mitochondria-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…In this study a single animal model of RVF was explored. A recent study by our group evaluated the ability of the computational model to predict pathophysiology in three different experimental models of PH ( Pewowaruk et al, 2018 ). Here we focused on one PH model to enable in-depth investigation of the effect of a potential therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study a single animal model of RVF was explored. A recent study by our group evaluated the ability of the computational model to predict pathophysiology in three different experimental models of PH ( Pewowaruk et al, 2018 ). Here we focused on one PH model to enable in-depth investigation of the effect of a potential therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The multiscale computational model does provide the ability to investigate interventricular interactions allowing for consideration of LV function as a key variable when experimental results are available. Recent work by our group has explored the impact of LV myocardial infarction on RV function using simulations ( Pewowaruk et al, 2018 ). Despite these limitations, this novel study highlights that impaired myocyte force generation previously shown to be a cellular feature of RVF appears to drive impaired hemodynamic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico modelling facilitates parametric analysis of the relative contribution of isolated remodeling events to RV dysfunction; something that would be otherwise time-consuming or impractical to measure experimentally. The multi-scale in silico models used to study RV function range from lumped parameter hemodynamic models of the pulmonary vasculature (Grant and Paradowski, 1987) to organ and tissue-level models incorporating 3D animal/patient-specific biventricular geometries (Finsberg et al, 2019), structurally detailed fiber-level models (Gomez et al, 2017), and cell/molecularlevel models coupling mitochondrial mechanoenergetics to cross-bridge cycling and cardiomyocyte contractile dynamics (Pewowaruk et al, 2018). For a detailed review on multi-scale modeling of RV-PA mechanics in PAH, please refer to the recent work by .…”
Section: In Silico Modeling Of Rv Biomechanics In Pahmentioning
confidence: 99%
“…Pulmonary arterial hypertension has been shown to result in RV remodeling at different scales, from changes in organ-level hemodynamics to tissue stiffening, fiber reorientation, and altered myocyte contractility and mitochondrial energetics (Hill et al, 2014;Avazmohammadi et al, 2017a;Pewowaruk et al, 2018;Sharifi Kia et al, 2020). Mechanical stimuli play a key role in RV remodeling in response to pressure overload and biomechanical analysis of RV pathophysiology has drawn significant attention over the past years.…”
Section: Introductionmentioning
confidence: 99%